Whole-cell response of coronavirus-infected BMDCs through proteomic and transcriptomic analyses - Ji, Yanxi; Zhang, Yuzhen; Tong, Yongjia; Cao, Liu; Zeng, Lanyi; Xu, Yiran; Guo, Xiao; Xu, Tiefeng; Tang, Zhidong; Zhang, Zhen; Guo, Lin; Guo, Deyin; et al. (Frontiers in Immunology, 2025)
IntroductionUnderstanding the intricacies of the host inflammatory response to coronaviruses is essential for developing effective therapeutic strategies to mitigate the severe consequences of these infections. Various coronaviruses can trigger the host immune response, leading to highly similar inflammatory reactions. The mouse hepatitis virus (MHV), which belongs to the same group of beta-coronaviruses as SARS-CoV-2 and induces high pathogenicity in mice, typically serves as a safety model for investigating highly pathogenic coronavirus infections, replication, and virus-host interactions.MethodsIn this study, we conducted a comprehensive analysis of the transcriptome and proteome of mouse bone marrow dendritic cells (BMDCs) infected with MHV.ResultsWe characterized the global gene changes at both the mRNA and protein levels following viral infection, identifying ten genes involved in various anti-MHV biological processes. Furthermore, by integrating our findings with relevant published data on SARS-CoV-2 infection in cells, we observed significant similarities in the responses to MHV and SARS-CoV-2, particularly regarding immune and inflammatory responses.DiscussionThese findings underscore how our research enhances the understanding of global gene expression alterations during coronavirus infection and facilitates the identification of novel antiviral targets.